(untitled) (Indian Journal of Public Health Research & Development, 2025)
Non-communicable diseases (NCDs) represent one of the most pressing and intricate public health issues. This study aimed to verify the dietary knowledge of female university students regarding NCDs. This was a descriptive type of cross-sectional study with 385 female university students of Dhaka, Bangladesh. Data were gathered by pre-tested and semi-structured questionnaires. Analysis was performed by using multivariate techniques followed by regression modeling. This study reflected that the majority of the female students belonged to the age group <22 years. The study found that 77% of the respondents had poor knowledge of preventive diets to combat NCDs. It was observed that the highest level of poor knowledge was about the dietary policies that cause NCDs (85.7%) and benefits of fruits & vegetables intake to combat NCDs (83.4%) among female university students. Also, the highest level of poor knowledge is significantly (p<0.05) related to the students who did not have any family history of NCDs (AOR=2.57) and also 3rd year group (AOR=2.34).This study showed that few female university students had overall good knowledge, and the state of information regarding preventative diet to combat NCDs was unsatisfactory. This study discovered that several relevant predictors under socio-demographic repercussions were highly significant in relation to inadequate knowledge.